VISUAL-MEASURING MACHINERY AND TECHNOLOGY OF SIZE CONTROL IN FOUNDRY - E. I. Marukovich; A. P. Markov; V. F. Gogolinski; A. A. Alexandrovich; A. V. Konov; E. V. Beljanko (Литьë и металлургия)
The contact-contactless and contactless methods and visual-measuring means of size control in foundry and other fields are examined.